Interpreting radial correlation Doppler reflectometry using gyrokinetic simulations. (1st May 2022) - Ruiz Ruiz, J; Parra, F I; Hall-Chen, V H; Christen, N; Barnes, M; Candy, J; Garcia, J; Giroud, C; Guttenfelder, W; Hillesheim, J C; Holland, C; Howard, N T; et al.
Abstract: A linear response, local model for the DBS amplitude applied to gyrokinetic simulations shows that radial correlation Doppler reflectometry measurements (RCDR, Schirmer et al 2007 Plasma Phys. Control. Fusion 49 1019) are not sensitive to the average turbulence radial correlation length, but to a correlation length that depends on the binormal wavenumber k ⊥ selected by the Doppler backscattering (DBS) signal. Nonlinear gyrokinetic simulations show that the turbulence naturally exhibits a nonseparable power law spectrum in wavenumber space, leading to a power law dependence of the radial correlation length with binormal wavenumber l r ∼ C k ⊥ − α ( α ≈ 1 ) which agrees with the inverse proportionality relationship between the measured l r and k ⊥ observed in experiments (Fernández-Marina et al 2014 Nucl. Fusion 54 072001). This new insight indicates that RCDR characterizes the eddy aspect ratio in the perpendicular plane to the magnetic field. It also motivates future use of a nonseparable turbulent spectrum to quantitatively interpret RCDR and potentially other turbulence diagnostics. The radial correlation length is only measurable when the radial resolution at the cutoff location W n satisfies W n ≪ l r, while the measurement becomes dominated by W n for W n ≫ l r . This suggests that l r is likely to be inaccessible for electron-scale DBS measurements ( k ⊥ ρ s > 1 ). The effect of W n on ion-scale radial correlation lengths could be nonnegligible.